Extracellular Vesicles Reflect the Efficacy of Wheatgrass Juice Supplement in Colon Cancer Patients During Adjuvant Chemotherapy - Avisar, Adva; Cohen, Miri; Brenner, Benjamin; Bronshtein, Tomer; Machluf, Marcelle; Bar-Sela, Gil; Aharon, Anat (Frontiers in Oncology, 2020)
Introduction: Colorectal cancer is the third most common type of cancer, accounting for 10% of all cancer cases. Adjuvant chemotherapy is recommended in stage II-III colorectal cancer. Wheatgrass juice (WGJ) from wheat seeds has high nutritional values, may induce synergistic benefits to chemotherapy and may attenuate chemotherapy-related side effects. Extracellular vesicles (EVs) are subcellular membrane blebs. EVs include exosomes (generated in the endosome, in size <150nm) and microvesicles (shed from the plasma cell membrane) provide information on their parental cells and play a role in intercellular communication. We aimed to elucidate the effects of chemotherapy administration with supportive treatment of WGJ on colorectal cancer patients’ EVs characteristics. Methods: EVs were isolated from the blood samples of 15 healthy controls (HC) and 50 colorectal cancer patients post-surgery, treated by chemotherapy, with or without additional daily WGJ. Blood samples were taken before, during, and at the end of chemotherapy. EVs were characterized by size, concentration, membrane antigens and cytokine content using nanoparticle-tracking analysis, western blot, flow cytometry, and protein array methods. Results: EVs were found to be similar by size and concentration with reduced levels of exosome markers (CD81) on samples at the end of combined treatment (chemotherapy and WGJ). Higher levels of endothelial EVs, which may indicate impairment of the vascular endothelial cells during treatment, were found in colorectal cancer patients treated by chemotherapy only compared to those with chemotherapy and daily WGJ. Also, EVs thrombogenicity was lower in patients added WGJ compared to patients who had only chemotherapy (levels of tissue factor p=0.029 and endothelial protein C receptor p=0.005). Following treatments, levels of vascular endothelial growth factor receptors (VEGFR-1) and the majority of growth-factors/pro-inflammatory cytokines were higher in EVs of patients treated by chemotherapy only than in EVs obtained from patients with the combined treatment. Conclusions: Daily consumption of WGJ during chemotherapy may reduce vascular damage and chemotherapy-related thrombogenicity, growth factors and cytokines, as reflected by the characteristics of patient's EVs.